Cassava at a glance - Sarvanan, R; Ravi, V; George, James (Indian Horticulture, 2019)
Perennial shrub, cultivated as annual for its starch rich storage roots/tubers. Cultivated as rainfed as well irrigated crop under wide variety of soils and climatic conditions. Fresh tubers are directly consumed after boiling or utilized for production of industrial starch, sago and wafers. Cassava is a hardy crop resilient to climate change, suitable for low input agriculture and food security.